Lower Limb Amputations among Diabetics Admitted with Diabetic Foot Disorders in Three Major Hospitals in Jeddah, Saudi Arabia - Wail A. Tashkandi,; Mohammed M. Badri,; Sami M. Badawood,; Nashat A. Ghandourah,; Ahmad M. Kinsarah,; Hasan A. Alzahrani, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Diabetic foot disorders are responsible for at least 50% of limb amputations in Jeddah, and usually associated with long hospital stay and low rehabilitation rate. To identify the percentage of lower limb amputations in patients admitted with diabetic foot disorders, a multicentre retrospective study was conducted over one year in Jeddah area in three major public hospitals. Two hundred and twenty-nine files were reviewed to identify the percentage of lower limb amputations among diabetic patients admitted with foot disorders. One hundred and twenty-eight records (the total number of patients who underwent amputations) were reviewed to obtain information about the presentation, associated factors, level of amputations, rates of post-operative complications, re-amputations, mortality, hospital stay and rehabilitation. Ulcer was the most common presentation (85.9%). Sixty percent of patients who were admitted with diabetic foot ended up with lower limb amputation. Toes amputation was the most common type followed by below knee then above knee amputation. Re-amputation, post-operative complications and mortality within 30 days were 3.9%, 4.7% and 7%, respectively. Only 12.5% of the amputees have been rehabilitated. Amputations on diabetics are a major health problem. Every effort should be made to avoid it particularly with limited resources for rehabilitation in developing countries